Four new species of the genus Eudarcia Clemens, 1880 (Lepidoptera: Meessiidae) from Crimea - Budashkin, Yuriy I.; Bidzilya, Oleksiy (Zootaxa, 2018)
Four species of the genus Eudarcia are described as new from Crimea: E. ajpetrica sp. nov., E. kimmeriella sp. nov., E. rutjani sp. nov. and E. zagulajevi sp. nov. All newly discovered species belong to the palanfreella-species group. The identification key, based on external and genitalia characters for the Eudarcia species from Crimea, is provided.